The Effect of Insight Marketing in Achieving Banking Brilliance - Mohammed, Safaa Tayyeh; Ali, Oday Hussein (South Asian Journal of Social Sciences and Humanities, 2025)
The study aims to find out the impact of the independent variable marketing, the insight and dimensions represented (future vision, actionable, commercial capabilities, credible, originality) in achieving the dependent banking brilliance and dimensions represented (brilliance in service and innovation, Glittering in knowledge, brilliance in leadership, through a sample of workers in commercial banks in the southern region. The questionnaires, where (200) versions of analyzing questionnaire were obtained from the workers of the commercial banks in the southern region, through the use of the (Smart PLS) program to test the hypotheses of the correlation of the study variables and obtain the results. One of the most important results of this study is that Insight Marketing contributes to achieving banking brilliance, through that insight helps the bank's top management to fully understand the market landscape and developments in a world of competition in financial institutions in general and the banking sector in particular.
Keywords: Insight Marketing; Banking Brilliance; Commercial banks; Performance